Combining Bottom-Up and Top-Down Mass Spectrometric Strategies for De Novo Sequencing of the Crustacean Hyperglycemic Hormone (CHH) from Cancer borealis - Ma, Mingming (2009)
The crustacean hyperglycemic hormone (CHH) is a 72-amino acid residue polypeptide with multiple physiological effects. The X-organ/sinus gland is the primary source for CHH and its family members. However, the amino acid sequence of CHH in Cancer borealis, a premier model system for neuromodulation, has not been characterized. In this study, a novel hybrid strategy combining “bottom-up” and “top-down” methodologies enabled direct sequencing of CHH peptide in the sinus gland of C. borealis. Multiple mass spectrometry (MS)-based techniques were employed to characterize the CHH peptide, including direct tissue analysis by MALDI FT-ICR MS, de novo sequencing of tryptic digested CHH by nano-LC-ESI Q-TOF MS and intact CHH analysis by LC FT-ICR MS. In-trap cleaning removed the extensive matrix adducts of CHH in the direct tissue analysis by MALDI FT-ICR MS. Fragmentation efficiency of the intact CHH was drastically improved after the reduction-alkylation of the disulfide bonds. The sequence coverage was further enhanced by employing multiple complementary fragmentation techniques. Overall, this example is the largest neuropeptide de novo sequenced in C. borealis by mass spectrometric methods.